2008
DOI: 10.1029/2007jd009538
|View full text |Cite
|
Sign up to set email alerts
|

Origin of surface and columnar Indian Ocean Experiment (INDOEX) aerosols using source‐ and region‐tagged emissions transport in a general circulation model

Abstract: [1] We study the relative influence of aerosols emitted from different sectors and geographical regions on aerosol loading in south Asia. Sectors contributing aerosol emissions include biofuel and fossil fuel combustion, open biomass burning, and natural sources. Geographical regions include India (the Indo-Gangetic plain, central India, south India, and northwest India), southeast Asia, east Asia, Africa-west Asia, and the rest of the world. Simulations of the Indian Ocean Experiment (INDOEX), from January to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 41 publications
1
25
0
Order By: Relevance
“…21. These strong gradients, including the sharp gradient across the ITCZ, were first noted in measurements made on the pre-INDOEX and INDOEX ship cruises (e.g., Rhoads et al, 1997;Moorthy et al, 1997;Jayaraman et al, 1998Jayaraman et al, , 1999Jayaraman et al, , 2001Satheesh et al, 1998;Naja et al, 1999;Stehr et al, 2002;Quinn et al, 2002;Chand et al, 2001Chand et al, , 2003Kamra et al, 2003;Norman et al, 2003;Nair et al, 2004;Naja et al, 2004), as well as in aircraft observations during INDOEX (e.g., Ramanathan et al, 2001;Reiner et al, 2001;Gabriel et al, 2002a;Pelon et al, 2002;de Reus et al, 2002), and shortly thereafter were corroborated to be a general feature of the broader region based on numerous pieces of evidence, including further in situ observations, satellite retrievals and model simulations (e.g., Rajeev et al, 2000Rajeev et al, , 2004Rajeev and Ramanathan, 2001;Collins et al, 2001Collins et al, , 2002de Laat et al, 2001a, b;Lelieveld et al, 2001;Lawrence et al, 2003a;Minvielle et al, 2004a, b;Moorthy et al, 2005a;Satheesh et al, 2006a, b;Vinoj et al, 2007;Verma et al, 2008). In addition to this generally strong gradient of pollutants in the SAW-ABC, these observations and modeling studies have also shown a very abrupt transition between the polluted NH air masses and more pristine SH air in the MBL at the ITCZ, which can be considered a "chemical ITCZ" …”
Section: Transit Times Lofting In the Itcz And Interhemispheric Exchmentioning
confidence: 99%
“…21. These strong gradients, including the sharp gradient across the ITCZ, were first noted in measurements made on the pre-INDOEX and INDOEX ship cruises (e.g., Rhoads et al, 1997;Moorthy et al, 1997;Jayaraman et al, 1998Jayaraman et al, , 1999Jayaraman et al, , 2001Satheesh et al, 1998;Naja et al, 1999;Stehr et al, 2002;Quinn et al, 2002;Chand et al, 2001Chand et al, , 2003Kamra et al, 2003;Norman et al, 2003;Nair et al, 2004;Naja et al, 2004), as well as in aircraft observations during INDOEX (e.g., Ramanathan et al, 2001;Reiner et al, 2001;Gabriel et al, 2002a;Pelon et al, 2002;de Reus et al, 2002), and shortly thereafter were corroborated to be a general feature of the broader region based on numerous pieces of evidence, including further in situ observations, satellite retrievals and model simulations (e.g., Rajeev et al, 2000Rajeev et al, , 2004Rajeev and Ramanathan, 2001;Collins et al, 2001Collins et al, , 2002de Laat et al, 2001a, b;Lelieveld et al, 2001;Lawrence et al, 2003a;Minvielle et al, 2004a, b;Moorthy et al, 2005a;Satheesh et al, 2006a, b;Vinoj et al, 2007;Verma et al, 2008). In addition to this generally strong gradient of pollutants in the SAW-ABC, these observations and modeling studies have also shown a very abrupt transition between the polluted NH air masses and more pristine SH air in the MBL at the ITCZ, which can be considered a "chemical ITCZ" …”
Section: Transit Times Lofting In the Itcz And Interhemispheric Exchmentioning
confidence: 99%
“…Elevated aerosols loading was observed in a remote marine environment over the Arabian Sea during INDOEX 1999. The chemical transport models have been used widely for atmospheric simulations over southern Asia during the INDOEX period (Rajeev et al, 2000;Rasch et al, 2001;Podgorny and Ramanathan, 2001;Reddy et al, 2004;Verma et al, 2008Verma et al, , 2012, and have shown a predominance of sulphate in the south Asian region. Most of the INDOEX studies emphasize the underestimated impact of aerosols on climate Ramanathan et al, 2002;UNEP, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Aerosol transport and its impact on radiative forcing were estimated over the tropical Indian Ocean during INDOEX (Krishnamurty et al, 1998;Podgorny et al, 2000;Rajeev et al, 2001). General circulation model (GCM) simulations over south Asia during the INDOEX period with the high resolution regional emissions information (Reddy et al, 2004;Verma et al, 2008Verma et al, , 2012 indicate the likely contribution of emissions from regions outside India to aerosol loading over the Indian subcontinent and adjoining oceans.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to pollution, the aerosol load of northern India and Nepal is affected by important natural contributions. Mineral dust from the surrounding West Asian deserts (or even from the Sahara and Arabian ones) can constitute a large fraction of the aerosol optical depth (AOD), particularly during the premonsoon season (March-May), when dust is observed to mix with anthropogenic pollution (e.g., Shresta et al, 2000;Chinnam et al, 2006;Prasad and Singh, 2007;Liu et al, 2008;Verma et al, 2008). In this context, the assessment of the radiative effects of anthropogenic vs. natural aerosols in this region represents an intricate task (e.g., Dey and Tripathi, 2008).…”
Section: Introductionmentioning
confidence: 99%